PENGARUH MANAJEMEN KOMPLAIN DAN BEBAN KERJA TERHADAP STRESS DAN DAMPAKNYA PADA KINERJA PEGAWAI DINAS PERHUBUNGAN ACEH BARAT (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2019)
This study aims to determine the direct or indirect influence of complaints management and workload on work stress and its impact toward the employees’ performance in the Transportation Department of West Aceh Regency. The population is all employees who work at TransportationDepartment of West Aceh Regency with a total of 110 people. Because the size of the population is sufficient and affordable then the research sample is the entire population of employees. Data collection is performed by distributing an open questionnaire. Primary data were analyzed using SEM (Structural Equation Modeling) analysis technique. The result of the research shows that complaint management has negative and insignificant effect on work stress at Transportation Department of West Aceh Regency. Workload has positive and insignificant effect to work stress. Complaint management and workload have a positive and significant effect on employees’ performance. Work stress has a negative and significant effect on the employees’ performance at Transportation Department of West Aceh Regency. Work stress plays a role in increasing the positive influence between complaints management and employees’ performance. Work stress plays a role in increasing the negative influence between workload on employee performance at the Transportation Department of West Aceh Regency.